Impact of an interdisciplinary malnutrition quality improvement project at a large metropolitan hospital - Kelsey Jones Pratt (BMJ Open Quality, 2020)
As many as 50% of hospitalised patients are estimated to be malnourished or at risk of malnutrition on hospital admission, but this condition often goes unrecognised, undiagnosed and untreated. Malnutrition is associated with an elevated need for continued medical interventions, higher costs of care and increased patient safety risks. Tampa General Hospital (TGH), a large teaching hospital in the southeastern USA, initiated a project to improve the quality of patient care at its institution. They did this first by focusing on improving the care quality for their malnourished patients (or patients who were at risk of malnourishment) and by using elements of the national Malnutrition Quality Improvement Initiative (MQii) Toolkit as a mechanism to measure and improve quality. The aim of this study was to evaluate the impact of quality improvement interventions on patient length of stay (LOS), infection rates and readmissions, particularly for malnourished patients. The structure of the MQii and the use of the MQii Toolkit helped staff members identify problems and systematically engage in quality improvement processes. Using the MQii Toolkit, TGH implemented a multipronged approach to improving the treatment of malnourished patients that involved creating interdisciplinary teams of staff and identifying gaps in care that could be improved through a series of changes to hospital-wide clinical workflows. They enhanced interdisciplinary coordination through increased dietitian engagement, the use of electronic health record alerts and new surgical protocols. These interventions lasted 8 months in 2016 and data reported here were collected from 985 patients before the interventions (2015) and 1046 patients after the interventions (2017). The study examines how these process changes affected LOS, infection rates and readmissions at TGH. Following implementation of these quality improvement processes, patients who were malnourished or at risk of malnutrition had a 25% reduction in LOS (from 8 to 6 days, p<0.01) and a 35.7% reduction in infection rates (from 14% to 9%, p<0.01). No statistically significant changes in readmission rates were observed. This study adds to a growing body of literature on quality improvement processes hospitals can undertake to better identify and treat malnourished patients. Hospitals and health systems can benefit from adopting similar institution-wide, quality improvement projects, while policy-makers’ support for such programmes can spur more rapid uptake of nutrition-focused initiatives across care delivery settings.